(untitled) (Journal of the College of Basic Education, 2023)
The natural constituents in the Abu Shareesh basin are represented by the geological structure, surface features, and climate, where the influence of these constituents varies in the formation of landforms, as the geological structure had a clear role in the study area. Stratigraphically, the dominant rocks in the region are sedimentary rocks, and the study of the surface features aims at topographic and geomorphological analysis in the basin, in order to know the spatial variation that gives a clear idea of the slopes and the direction of the slope, and we infer from it that there is a general slope in the region that extends from the southwest towards the northeast, In addition to studying the climate with its elements (Solar radiation, temperatures, wind, precipitation) and their impact on the study area.